Ethnopharmacology – active substances and medicines - G, Odontuya (Bulletin of the Institute of Chemistry and Chemical Technology, 2019)
Ethnopharmacological evidence and knowledge of medicinal plants, as well as their traditional usage in folk medicine could become an important guide for discovering and studying their pharmacologically active substances. Of the 122 officially recognized medicinal plant-based medicines worldwide, 80 % are derived from either ethnomedical practice or traditional usages by the local populations. Consequently, this illustrates the effectiveness of identifying active substances from the ethnomedical practices of the related medicinal plants. Today, pharmaceutical companies have started to direct research activities for discovering active compounds from natural sources, including medicinal plants, due to an increase in the lack of precise medications available for treating certain medical complications, as well as a comparatively high level of side effects and toxicity in synthetic medicines. Угсаатны эм судлал –эмийн идэвхт бодис, шинэ эм бэлдмэлийн эх сурвалж болох нь Хураангуй: Эмийн ургамлыг уламжлалт анагаах ухаанд хэрэглэдэг талаарх угсаатны эм судлалын мэдлэг, мэдээлэл нь ургамлаас эмчилгээний идэвхтбодисыг ялган судлах, ашиглахадчухал удирдамж болдог. Эмийн ургамлаас гарган авсан 122 бодис нь эм болж дэлхийн эмийн зах зээлд нийлүүлэгдсэн байдаг бөгөөд эдгээрийн 80 % нь тухайн өвчнийг анагаахад орон нутгийн ард түмний хэрэглэж заншсан ургамлаас ялгагдаж, угсаатны эм судлалын судалгааны үр дүнд бүтээгдсэн онцлогтой. Орчин үед зарим өвчний эмчилгээнд тохирох эм бэлдмэл одоо болтол гараагүй, нийлэг эмийн гаж нөлөө, хоруу чанар их зэрэг олон шалтгааны улмаас эмийн компаниуд байгалиас, ургамлаас эмийн идэвхтбодисыг шинээр илрүүлэн эм бэлдмэл гарган авах хандлага, сонирхол улам бүр өсөж байна. Түлхүүр үг: Ургамал, угсаатны ам судлал, эмийн идэвхт бодис, эм бэлдмэл